Anti-Inflammatory and Anti-Fibrotic Effects of Human Amniotic Membrane Mesenchymal Stem Cells and Their Potential in Corneal Repair. (10th September 2018) - Navas, Alejandro; Magaña-Guerrero, Fátima Sofía; Domínguez-López, Alfredo; Chávez-García, César; Partido, Graciela; Graue-Hernández, Enrique O.; Sánchez-García, Francisco Javier; Garfias, Yonathan
Abstract : Acute ocular chemical burns are ophthalmic emergencies requiring immediate diagnosis and treatment as they may lead to permanent impairment of vision. The clinical manifestations of such burns are produced by exacerbated innate immune response via the infiltration of inflammatory cells and activation of stromal fibroblasts. New therapies are emerging that are dedicated to repair mechanisms that improve the ocular surface after damage; for example, transplantation of stem cells (SC) has been successfully reported for this purpose. The pursuit of easily accessible, noninvasive procedures to obtain SC has led researchers to focus on human tissues such as amniotic membrane. Human amniotic mesenchymal SC (hAM-MSC) inhibits proinflammatory and fibrotic processes in different diseases. hAM-MSC expresses low levels of classical MHC-I and they do not express MHC-II, making them suitable for regenerative medicine. The aim of this study was to evaluate the effect of intracameral injection of hAM-MSC on the clinical manifestations, the infiltration of inflammatory cells, and the activation of stromal fibroblasts in a corneal alkali-burn model. We also determined the in vitro effect of hAM-MSC conditioned medium (CM) on α-SMA + human limbal myofibroblast (HLM) frequency and on release of neutrophil extracellular traps (NETs). Our results show that intracameral hAM-MSC injection reduces neovascularization, opacity, stromal inflammatory cell infiltrate, and stromal α-SMA + cells in our model. Moreover, in in vitro assays, CM from hAM-MSC decreased the quantity of α-SMA + HLM and the release of NETs. These results suggest that intracameral hAM-MSC injection induces an anti-inflammatory and anti-fibrotic environment that promotes corneal wound healing.